Exercise cardiac function in endurance-trained males versus females - Wiebe, C. G.; Gledhill, N.; Warburton, D. E.; Jamnik, V. K.; Ferguson, S. (Clinical Journal of Sport Medicine, 1998)
OBJECTIVE: To examine and compare the exercise cardiac function of endurance-trained (ET) women and men. PARTICIPANTS: Six ET women aged 20 to 29 years (mean VO2max = 64 ml.kg-1.min-1) and 9 ET men aged 20 to 29 years (mean VO2max = 69 ml.kg-1.min-1) were included in the study. MAIN OUTCOME MEASURES: Cardiac output (Q), stroke volume (SV), diastolic filling rate (DFR), and left ventricular ejection rate (LVER) were compared at rest and during exercise at heart rates (HRs) of 110, 130, 150, 170 bpm, and max. Resting blood volume (BV) and hemoglobin concentration ([Hb]) were also compared. RESULTS: Compared to women, men had a higher BV and [Hb]. At HRmax, men had a higher Q (31.0 +/- 0.6 versus 24.1 +/- 0.9 l.min-1), SV, DFR, and LVER than women. When expressed relative to body mass (kg), there were no gender differences in SVmax, and women had a significantly higher a-v DO2max (approximately 19%) than men. The SV of the men and women did not plateau at a submaximal level but continued to increase progressively to HRmax. During maximal exercise, the DFR was significantly faster than the LVER in the men and the women. CONCLUSIONS: When ET men and women are matched for body mass, the gender difference in SVmax is reduced so that it is no longer statistically significant. However, there are still significant gender differences in Q, DFR, LVER, BV, and [Hb] that contribute to a higher VO2max (ml.kg-1.min-1) in ET men compared to women. To augment SVmax, women and men rely to a greater extent on diastolic filling than on left ventricular emptying.